2014
DOI: 10.1021/bi500758u
|View full text |Cite
|
Sign up to set email alerts
|

Converting a Binding Protein into a Biosensing Conformational Switch Using Protein Fragment Exchange

Abstract: Biosensors can be used in applications ranging from identifying disease biomarkers to detecting spatial and temporal distributions of specific molecules in living cells. A major challenge facing biosensor development is how to functionally couple a biological recognition domain to an output module so that the binding event can be transduced to a visible and quantifiable signal [e.g., Förster resonance energy transfer (FRET)]. Most designs achieve coupling by means of a binding protein that changes conformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…Binding to cAbl kinase co-operatively stabilized the assembly of the FN3-based binder from two partial fragments, and was resolved by intermolecular FRET between YFP and CFP [34]. This promises to be a generic method for converting globular binding scaffolds into allosteric fluorescent sensors.…”
Section: Box 1 Challenges Of Engineering Protein Switchesmentioning
confidence: 98%
“…Binding to cAbl kinase co-operatively stabilized the assembly of the FN3-based binder from two partial fragments, and was resolved by intermolecular FRET between YFP and CFP [34]. This promises to be a generic method for converting globular binding scaffolds into allosteric fluorescent sensors.…”
Section: Box 1 Challenges Of Engineering Protein Switchesmentioning
confidence: 98%
“…In the former scenario the solution is to introduce tuning mutations into the N ′-frame instead of the N- frame. The expectation is that Δ θ will initially increase and then approach a maximum value as the N ′-fold is progressively destabilized by packing mutations of increasing severity [3]. Any one of these variants can be used for sensing, although for the typical case in which a balance between high Δ θ and low K d is desired, the mutant that yields outcome (i) is selected as the final optimized product.…”
Section: Step 3 Of Aff Protocol: Optimizationmentioning
confidence: 99%
“…2. Our simulations have shown that it is possible, although highly unlikely, that a ternary complex will form in the absence of a packing mutation, as the entropic barrier for intermolecular folding is usually too large to be overcome by ligand-binding energy alone [3]. A more realistic concern is that the binary complex of full-length POI and fragment will form without ligand present.…”
Section: Step 3 Of Aff Protocol: Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a biosensor is a protein containing duplicated segments in which only one of the two fragments at a time is incorporated in the folded protein. Stratton et al developed the alternate frame folding (AFF) strategy from a wild-type fold (N) to its circularly-permuted fold (N’) to build a switchable protein based on conformational changes [33,34,35,36,37,38]. Although MEF and AFF are incorporated into the folding-unfolding switch design, experimental studies on their switch mechanisms and the details of conformational variations at atomic level are limited so far.…”
Section: Introductionmentioning
confidence: 99%